Fear Of Talking In Educational Domain - Amira Benmakhlouf (Al-Lisaniyyat)
The language is a human system of communication that uses arbitrary signals such as voice sounds, gestures or written symbols and the study of language is called linguistics, it occupies the largest part in our lives, without her we cannot share any ideas, it is the essential tool, Moreover the process of communication enable us to open up on the world and other cultures and other civilizations, in the other hand it may be exposed to several obstacles such as “fear of talking” ,that It will be the subject of my study, particularly in educational domain where the student is inclosed on himself and has no support,… Furthermore I will treat the causes the reasons and how does this anxiety effects on the nature of people of all categories (whether in regular talks or the educational field) ,and how does the scientists look at the fear of facing public to help find out how we can control it